Polyadenylation of maternal mRNA during oocyte maturation: poly(A) addition in vitro requires a regulated RNA binding activity and a poly(A) polymerase. - Fox, C A (1992)
Specific maternal mRNAs receive poly(A) during early development as a means of translational regulation. In this report, we investigated the mechanism and control of poly(A) addition during frog oocyte maturation, in which oocytes advance from first to second meiosis becoming eggs. We analyzed polyadenylation in vitro in oocyte and egg extracts. In vivo, polyadenylation during maturation requires AAUAAA and a U-rich element. The same sequences are required for polyadenylation in egg extracts in vitro. The in vitro reaction requires at least two separable components: a poly(A) polymerase and an RNA binding activity with specificity for AAUAAA and the U-rich element. The poly(A) polymerase is similar to nuclear poly(A) polymerases in mammalian cells. Through a 2000-fold partial purification, the frog egg and mammalian enzymes were found to be very similar. More importantly, a purified calf thymus poly(A) polymerase acquired the sequence specificity seen during frog oocyte maturation when mixed with the frog egg RNA binding fraction, demonstrating the interchangeability of the two enzymes. To determine how polyadenylation is activated during maturation, we compared polymerase and RNA binding activities in oocyte and egg extracts. Although oocyte extracts were much less active in maturation-specific polyadenylation, they contained nearly as much poly(A) polymerase activity. In contrast, the RNA binding activity differed dramatically in oocyte and egg extracts: oocyte extracts contained less binding activity and the activity that was present exhibited an altered mobility in gel retardation assays. Finally, we demonstrate that components present in the RNA binding fraction are rate-limiting in the oocyte extract, suggesting that fraction contains the target that is activated by progesterone treatment. This target may be the RNA binding activity itself. We propose that in spite of the many biological differences between them, nuclear polyadenylation and cytoplasmic polyadenylation during early development may be catalyzed by similar, or even identical, components.